Bridging the Gap in Eastern European Cystic Fibrosis Care: How Newborn Screening and Advanced CFTR Modulation Shape the Clinical Landscape in Western Romania - Cristian Phillip Marinău; Cristian Sava; Alin Iuhas; Ioana Mihaiela Ciucă; Liviu Laurențiu Pop; Larisa Niulaș; Ariana Szilagyi; Alexandru Jurca; Claudia Maria Jurca (Children, 2026)
Background/Objectives: Cystic fibrosis (CF) care in Romania underwent a major transition in 2022 with the near-simultaneous introduction of newborn screening (NBS) and national reimbursement of CFTR modulator therapies. This study aimed to compare age at diagnosis between screen-detected and symptom-detected patients, describe clinical outcomes according to modulator status, and estimate regional case-detection ratios in Bihor County. Methods: This was a retrospective observational study with cross-sectional assessment of 46 CF patients followed at the National Cystic Fibrosis Centre in Timișoara during 2025. Nonparametric methods were used for exploratory comparisons. Case-to-live-birth ratios were estimated for pre-screening (2008–June 2022) and post-screening (July 2022–2024) periods in Bihor County. Results: Median age was 8.96 years (IQR 7.06–15.25); 58.7% of patients were male. Screen-detected patients (n = 5) were diagnosed earlier than symptom-detected patients (median 0.00 vs. 0.60 years; p = 0.016). F508del was present in 65.2% of alleles, with 22 distinct variants identified. Modulator therapy was received by 84.8% (76.1% elexacaftor/tezacaftor/ivacaftor). Median percent-predicted FEV1 (ppFEV1) was 99.0% (n = 38), comparable to ECFSPR 2024 pediatric values, while median BMI Z-score (−0.32) remained below Western European benchmarks. Chronic Pseudomonas aeruginosa and MRSA colonization rates were 11.4% (pediatric) and 15.2% (overall), respectively. ppFEV1 correlated strongly with BMI Z-score (ρ = 0.625, p < 0.001). The Bihor County case-to-live-birth ratio was 1:7820, with a descriptive 1.45-fold increase post-NBS. Conclusions: CF characterization in western Romania demonstrates rapid modulator uptake and preserved lung function while highlighting persistent gaps in nutritional status, microbiological burden, and case detection relative to Western European populations. Longitudinal nationally representative studies are needed to confirm these findings.